The Relationship Between Integrative Self-Knowledge, Mindfulness, Self-Control, and Mental Health Parameters - Hajifathali, Fatemeh (2021)
Background: Self-regulating is a set of processes that controls or alters individuals’ behavior, emotion, and performance. We aimed to evaluate the relation between three components of self-regulating including integrative self-knowledge, mindfulness, self-control, and some variables of mental health and self-conscious emotions. Methods: A total of 233 Iranian university students voluntarily enrolled in the study. Seven questionnaire forms including Integrative Self-Knowledge Scale (ISKS), Attention Awareness Scale (MASS), Short Self Control Scale (SSCS), Costello & Comrey's Anxiety and Depression Scale, Rosenberg Self–Esteem Scale (RSES), Authentic Pride Scale (APS), and other as sham scale (OAS) were distributed to participants. The correlation between self-regulating variables, mental health, and self-conscious emotions were analyzed using Pearson's correlation coefficient test. Results: We found a negative correlation between self-regulating variables, depression, and anxiety. Our data also revealed that self-esteem positively related to integrative self-knowledge, mindfulness, and self-control. Among self-conscious emotions variables, authentic pride had a positive correlation with self-regulating variables whereas feelings of shame appeared a negative relationship with them. Conclusion: Integrative self-knowledge, mindfulness, and self-control as self-regulating components correlated to mental health and self-conscious emotions.